Assessment of the Impact of Zinc, Iron, and Vitamin D Deficiencies on the Prevalence of Dermatological Disorders among Males in Taiz, Yemen - Abdullah, Ahmed Mohammed Ahmed; Aljarmouzi, Mueataz Ameen Esmail Ali; Aljarmouzi, Fakhr Aldain Esmail Ali; Mohammed, Ayman Waheeb Ali; Mahyoub, Mohammed Ahmed Naji; Ali, Maher Abdulalkreem (University of Science and Technology, Sana’a, 2026)
Background: Micronutrients such as zinc, iron, and vitamin D play essential roles in maintaining skin integrity, immune function, and cellular repair. Deficiencies in these nutrients have been implicated in various dermatological disorders, yet limited data are available among Yemeni populations. Objective: This study aimed to assess the impact of zinc, iron, and vitamin D deficiencies on the prevalence and clinical characteristics of dermatological disorders among adult males in Taiz, Yemen. Methods: This was a cross-sectional study involving 47 male participants, including 30 cases with dermatological disorders and 17 apparently healthy controls. Demographic data, medical history, and clinical characteristics of skin diseases were recorded. Blood samples were collected to measure hemoglobin (Hb), serum zinc, serum iron, and vitamin D levels. Statistical analyses included independent sample t-tests, chi-square tests, and one-way ANOVA, with a significance level set at P < 0.05. Results: The most common dermatological manifestations among cases were redness (73.3%), hair loss (56.7%), and extensive skin dryness (50%). Eczema was the most frequent clinical diagnosis (29.4%) then hair loss (17.6). Serum zinc levels were significantly lower in cases compared to controls (59.37 ± 15.58 vs. 87.24 ± 17.96 µg/dL, P < 0.001). Hemoglobin levels were also significantly lower among cases (P < 0.001). Although serum iron and vitamin D levels were lower in cases than controls, these differences were not statistically significant. No significant association was observed between C-reactive protein (CRP) levels and skin disease. Additionally, micronutrient levels did not significantly vary according to disease duration or disease type. Disease Severity: Patients with chronic conditions lasting more than one year showed the lowest mean levels of iron, zinc, and vitamin D. Conclusion: Zinc deficiency and lower hemoglobin levels were significantly associated with dermatological disorders among males in Taiz, Yemen. These findings highlight the importance of assessing micronutrient status, particularly zinc, in patients presenting with skin diseases. Nutritional screening and appropriate supplementation may play a supportive role in the management and prevention of dermatological disorders.